Enablers for usage of the mobile wallet by msmes in rural India: Using the interpretive structural modelling approach - Reena Agrawal; Maneesh Yadav (Financial Internet Quarterly, 2024)
In today's digital era, it is all the more desirable that all businesses, whether gigantic or minor in operation, should adopt financial technology and grow their businesses within their region and outside of the region. The Micro, Small & Medium Enterprises (MSME) segment is the mainstay of the Indian economic environment thus it is crucial that MSME players adopt financial technol- ogy in their routine commercial transactions. The present research study was conducted to in- vestigate the enablers of usage of a Mobile Wallet by MSMEs in rural areas of India using inter- pretive structural modeling. It aims to categorize the foremost enablers and assess the relative relations between the recognized ten key enablers and proposes a hierarchical outline of vital enablers on MSME entrepreneurs from several hill states of India. The most prominent enabler that promoted the use of mobile wallets among MSME entrepreneurs included risk factors and perceived cost. The study suggested that multi-dimensional determinations are required to make certain of the use of mobile wallets by MSME entrepreneurs so that they can assess maxi- mum economic opportunities and support the fiscal expansion of the state and the country.
Keywords: MOG; 330; Mobile Wallet; Perceived Cost; Risk Factor; Merchant Support; Compliance